Genetic variation based on RAPD (Random Amplified Polymorphic DNA) markers in western tarsiers (Cephalopachus bancanus) from South Sumatra and Bangka Island - Pratiwi, Putri Rizki; Muharni, Muharni; Setiawan, Arum; Hanum, Laila; Yustian, Indra (Universitas Pakuan, 2024)
The western tarsier (Cephalopachus bancanus) is a nocturnal primate classified as Vulnerable by the IUCN. Understanding the genetic variation of tarsier populations in South Sumatra and Bangka Island is crucial for developing effective conservation strategies to protect this unique species. The research aims to determine the genetic variations of tarsiers from South Sumatra and Bangka Island by using 10 primers of the Random Amplified Polymorphic DNA (RAPD) molecular marker, namely ILO 525, ILO 1212, ILO 1204, OPE 16, OPE 17, OPE 19, OPF 06, OPF 04, OPY 03 and OPY 13. The RAPD primers utilized in this study are universal and effectively detect genetic diversity at interspecies and intraspecies levels. These primers have demonstrated the ability to produce clear and distinct electrophoresis band patterns in primates and other mammals. A total of six tissue samples were collected from Bangka Island, specifically from Petaling Village, Mendo Barat, and two additional samples were obtained from South Sumatra, originating from Selangit, Musi Rawas, and Padang Bindu, Ogan Komering Ulu. The Bangka Island samples were derived from a single population inhabiting a secondary forest characterized by shrubs and old rubber plantations. In contrast, the South Sumatra samples were obtained from secondary forest environments. Eight of the ten RAPD primers successfully amplified 89 DNA fragments, exhibiting a high degree of polymorphism. The genetic distance analysis, based on Dice coefficient values ranging from 0.000 to 0.629, revealed varying levels of genetic divergence among the samples. The bootstrap analysis further demonstrated that the relationships among all Western Tarsier (Cephalopachus bancanus) samples had a confidence level exceeding 50%. The observed high polymorphism reflects substantial genetic variability among the samples. RAPD markers thus offer a valuable tool for studies focusing on the relationships within closely related populations.